Borderline Brenner tumor with a concomitant mucinous tumor of the ovary: a case report - Ayık Aydın, Hülya; Bayramoğlu, Zeynep; Aydın, Armağan; Pestereli, Hadice Elif; Şimşek, Tayup (The European Research Journal, 2018)
Brenner tumors (BTs) are rare ovarian tumors which are a part of the epithelial stromal tumor group of ovarian neoplasms. Most of the BTs are benign and usually asymptomatic. BTs stand for the 1.4-2.5% of ovarian tumors. Of the BTs, not more than 2% exhibit characteristics of borderline (or malignant) BTs. Borderline BTs are usually bigger than benign BTs and individuals typically represent with symptoms related with an unilateral ovarian mass. BTs are often related with mucinous cystadenomas or seldomly cystadenocarcinomas. We present a case of borderline BT associated with a concomitant mucinous ovarian tumor.